IN VITRO ANTIDIABETIC POTENTIALS OF SIDA ACUTA, ABUTILON INDICUM AND MALVASTRUM COROMANDELIANUM - DINLAKANONT, NANTAPORN; PALANUVEJ, CHANIDA; RUANGRUNGSI, NIJSIRI (International Journal of Current Pharmaceutical Research, 2020)
Objective: Starch metabolizing enzyme inhibitors are able to retard postprandial glucose absorption. This study aimed to investigate the in vitro inhibitory activities of alpha-glucosidase and alpha-amylase of three Malvaceous weeds i.e. Sidaacuta Burm. f., Abutilon indicum (Linn.) Sweet and Malvastrumcoromandelianum (Linn.) Garcke. Methods: The stems, roots and leaves of S. acuta, A. indicum and M. coromandelianum were sequentially extracted in dichloromethane and methanol, respectively. All fractions were tested for the inhibitory activities on yeast alpha-glucosidase, rat intestinal alpha-glucosidase and porcine alpha-amylase. p-Nitrophenyl-α-D-glucopyranoside and 2-chloro-4 nitrophenol-α-D- maltotrioside were used as the substrate for glucosidase and amylase respectively. Results: The dichloromethane fraction of the roots and stems from A. indicum and dichloromethane as well as methanolic fractions of the stems of M. coromandelianum could inhibit yeast alpha-glucosidase compared to 1-deoxynojirimycin with the IC50 of 0.36, 0.45, 0.48, 0.48 and 0.58 mg/ml respectively. A. indicum root methanolic fraction had the highest inhibitory effect on rat alpha-glucosidase activity compared to 1-deoxynojirimycin with the IC50 of 0.08 and 0.11 mg/ml respectively. M. coromandelianum, the dichloromethane fraction of roots and the methanolic fraction of stems, showed the strongest effect on alpha-amylase inhibition compared to acarbose with the IC50 of 0.07, 0.07 and 2.7 mg/ml, respectively. Conclusion: S. acuta, A. indicum and M. coromandelianum dichloromethane and methanolic fractions of the root, stem and leaf parts demonstrated an appreciable inhibitory activity on alpha-amylase from porcine, alpha-glucosidase from Saccharomyces cerevisiae and from rat intestine compared to 1-deoxynojirimycin and acarbose.